The Papers of Thomas A. Edison New Beginnings, January 1885-December 1887 - Edison, Thomas A. (Johns Hopkins University Press, 2015)
This richly illustrated volume explores Edison's inventive and personal pursuits from 1885 to 1887.Two decades after the American Civil War, no name was more closely associated with the nation's inventive and entrepreneurial spirit than that of Thomas Edison. The restless changes of those years were reflected in the life of America's foremost inventor. Having cemented his reputation with his electric lighting system, Edison had decided to withdraw partially from that field. At the start of 1885, newly widowed at mid-life with three young children, he launched into a series of personal and professional migrations, setting in motion chains of events that would influence his work and fundamentally reshape his life. Edison's inventive activities took off in new directions, flowing between practical projects (such as wireless and high-capacity telegraph systems) and futuristic ones (exploring forms of electromagnetic energy and the convertibility of one to another). Inside of two years, he would travel widely, marry the daughter of a prominent industrialist and religious educator, leave New York City for a grand home in a sylvan suburb, and construct a winter laboratory and second home in Florida. Edison's family and interior life are remarkably visible at this moment; his papers include the only known diary in which he recorded personal thoughts and events. By 1887, the familiar rhythms of his life began to reassert themselves in his new settings; the family faded from view as he planned, built, and occupied a New Jersey laboratory complex befitting his status. The eighth volume of the series, New Beginnings includes 358 documents (chosen from among thousands) that are the most revealing and representative of Edison's work, life, and place in American culture in these years. Illustrated with hundreds of Edison's drawings, these documents are further illuminated by meticulous research on a wide range of sources, including the most recently digitized newspapers and journals of the day.